Implementing Alternative Dispute Resolution to Address Student Brawls in Padang Vocational Schools - Novran Juliandri Bhakti; Erianjoni Erianjoni; Afriva Khaidir; Delmira Syafrini (Journal of Educational Studies, 2025)
Student brawls represent a persistent form of youth violence in Indonesian vocational schools, particularly in Padang City, where conventional punitive approaches have failed to address underlying causes. This study examines the implementation of Alternative Dispute Resolution (ADR) in managing student conflict. Using a qualitative case study design across three vocational schools, data were collected through interviews, observation, and document analysis involving multiple stakeholders. Data analysis followed the interactive model of Matthew B. Miles and A. Michael Huberman, supported by NVivo coding procedures. The findings indicate that student brawls are shaped by the interaction of internal factors (emotional instability, self-recognition, and school prestige) and external factors (peer influence, family environment, senior and alumni roles, and social media). The study also identifies patterned characteristics of violence, including premeditation, strategic timing and location, intergenerational transmission, and the use of sharp weapons. ADR practices—such as mediation, dialogue, and restorative engagement—demonstrate effectiveness in reducing conflict intensity, restoring communication, and preventing recurrence. From a theoretical perspective, the findings are explained through Edwin Sutherland’s Differential Association Theory, which emphasizes that deviant behavior is learned through social interaction, including the transmission of motives, techniques, and rationalizations. The persistence of student brawls reflects the dominance of definitions favorable to violence within peer networks. This study concludes that ADR offers a more sustainable and humanistic approach by addressing the social learning processes underlying student violence, rather than relying solely on punitive control.